Comparative Study on 4-Legged Transmission Line Tower with Different Bracings by using STAAD Pro: Design and Comparison of 4-Legged Transmission Line Tower with Different Bracings (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of a transmission line tower is to support conductors carrying electrical power and one or two ground wires at suitable distances above the ground level and from each other. The transmission line towers cost about 28 to 43 per cent of the total cost of the transmission line. A transmission tower is a space truss and is an indeterminate structure.The increasing demand for electricity can be made more economical by developing different light weight configuration of transmission line tower.The present study reports the design and analysis of a steel lattice transmission line towers of a power system located in Pune. The design and analysis of the considered power system has been done using STAAD Pro. Under the design and analysis of the system, the effect of wind and earthquake loads were studied and the results so obtained were compared for wind zones III for four legged tower. Transmission line towers carry heavy electrical transmission conductors at a sufficient and safe height from ground. In addition to their self-weight they have to withstand all forces of nature like strong wind, earthquake load. The main objective of this project is to design and comparison between four legged 220 kV transmission line tower and its configuration as per Indian Standard (IS800-2007 and IS875-1987).